Vascular Epiphyte Diversity Differs with Host Crown Zone and Diameter, but Not Orientation in a Tropical Cloud Forest - Wang, Xixi (PLoS One, 2016)
Vascular epiphytes are important components of biological diversity in tropical forests. We measured the species richness and abundance of vascular epiphytes along four vertical crown zones and five horizontal orientations on 376 trees, as well as the diameter at breast height (DBH) of host trees in tropical cloud forests in Bawangling, Hainan, China. The relationship between vascular epiphyte species richness and host tree DBH was assessed using a generalized linear model. There were 1,453 vascular individual epiphytes attributed to 9 families, 24 genera and 35 species, with orchids and pteridophytes dominating. Both the species richness and abundance of epiphytes significantly differed among the four crown zones for all collections and each host tree, suggesting that vertical microhabitats contribute to the distribution of epiphytes on host trees. Neither epiphyte abundance nor species richness differed among the eastern, southern, western, and northern orientations for all host trees; however, both richness and abundance were significantly higher for epiphytes that encircled host tree trunks. This suggests that morphological and physiological characteristics of the tree, but not microclimates probably contribute to the distribution of epiphytes on host trees. Epiphyte species richness was positively correlated with tree DBH across the six host tree species studied, with increases in DBH among smaller trees resulting in larger increases in richness, while increases in DBH among larger host trees resulting in more modest increases in ephiphyte richness. Our findings contribute support for a positive relationship between epiphyte species richness and host tree DBH and provide important guidance for future surveys of epiphyte community development.